دور السياسات الثقافية في تعزيز عمل المؤسسة الجزائرية - علواني عومار; عرعار أنس (University of Eloued جامعة الوادي, 2024)
تعتبر السياسات الثقافية عبارة عن جملة من الآليات والإجراءات والتوجيهات التي تتخذها الحكومات أو المؤسسات لدعم وتعزيز النواحي الثقافية في مجتمع ما، خاصة من خلال دعم الفن والثقافة والمجتمع بكل ما فيه، وترتبط ارتباط وثيق بالمؤسسات الثقافية، وهنا تبرز أهمية هذه الدراسة التحليلية التي تهدف إلى دراسة السياسات الثقافية في المؤسسة الجزائرية الثقافية بصفة خاصة، من خلال تحليل بعض الدراسات في الموضوع والربط بالواقع المعاش. Abstract: Cultural policies are considered a set of mechanisms, procedures, and directives taken by governments or institutions to support and enhance the cultural aspects of a society, especially by supporting art, culture, and society with everything in it. They are closely linked to cultural institutions, and here the importance of this analytical study, which aims to study Cultural policies in the Algerian cultural institution in particular, from By analyzing some studies on the subject and linking it to the lived reality.
دراسة وصفية تحليلية للمؤسسات الثقافية
Keywords: السياسة الثقافية; المؤسسة الثقافية; cultural institution; institution; cultural policies